A identidade Ticuna: através da Coleção Nimuendajú do Museu Goeldi - Almeida, Tília Monte de (Museu Paraense Emílio Goeldi, 2023)
This paper studies the Ticuna Collection from the "Curt Nimuendajú" Technical Reserve of the Museu Paraense Emilio Goeldi and the pieces collected by the researcher Priscila Faulhaber in the year 2000. This research focuses on the technological processes used in the making of the masks, as well as the classification of the various motifs found in them. The analyzed pieces of the collection refer to the craft categories Ritual Dance Costume and Musical Instruments. The nomenclature of the mask motifs are of various shapes according to the geometric models, or they may be associated with certain animals (zoomorphic figures), plants (phytomorphic figures), elements of nature, designations inspired by objects from the culture itself or mythological figures, representations of contact, man (anthropomorphic figures) or objects, the musical instruments are classified as ediophone, aerophone, membranophone. In studies based on the accounts collected by researcher Priscila Faulhaber, it shows that a single motif can suffer diverse meanings. Each version presents a new interpretation of the cultural context, and the mythical character of this collection is perceptible. The study of the myths that make up the vision of a particular ethnic group, such as the Ticuna, shows that its members seek to elaborate their own image and the links between it and past moments, with which they identify.